Articulation of environmental education in the curricula of higher education institutions: a systematic review (2023)
The objective of this study was to characterize environmental education from the articulation in the curricula of Higher Education Institutions. For this, a qualitative descriptive systematic review was carried out. For the search, collection, and analysis of data, the Web of science database was taken into account as a specialized search engine, and 25 articles were chosen. The results produced make it evident that the way in which universities decide to face their responsibility for the achievement of the sustainable development goals may vary due to the autonomy that they have in the organization of their study plans, however, many are choosing for taking into account the transversality of environmental education in all professional fields considering comprehensive training and the role that each individual can play to achieve a sustainable and ecological country.